ANALISIS KELAYAKAN USAHA TERNAK KAMBING KACANG DI KECAMATAN MOYO HILIR - Yudhi Sanjaya, Muhammad; Hamdani, Asrul; Sudirman, Sudirman (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the financial and non-financial feasibility of a kacang goat farming business in Moyo Hilir District. The research method used was a survey method, with a purposive sampling or proportional random sampling method based on the livestock population. Data analysis was conducted quantitatively to assess financial feasibility using the Revenue Cost Ratio (R/C Ratio), Net Present Value (NPV), Internal Rate of Return (IRR), and Payback Period (PP) parameters, as well as qualitative analysis for non-financial aspects (market, technical, and management). The results showed that the average livestock owned was 30 goats. Financially, this business was declared feasible with an R/C ratio > 1, a positive NPV, and an IRR exceeding the prevailing interest rate. Non-financially, market and technical aspects in Moyo Hilir District strongly support the sustainability of this business thanks to the availability of local feed and high market demand.